Azoospermia factor C subregion of the Y chromosome - Mili Nailwal; Jenabhai B Chauhan (Wolters Kluwer Medknow Publications, 2017)
The azoospermia factor (AZF) region on the Y chromosome consists of genes required for spermatogenesis. Among the three subregions, the AZFc subregion located at the distal portion of AZF is the driver for genetic variation in Y chromosome. The candidate gene of AZFc is known as deleted in azoospermia gene, which is studied with interest because it is involved in germ cell development and most frequently deleted genes leading to oligozoospermia and azoospermia. Recently, two partial deletions in AZFc gr/gr and b2/b3 are characterized at the molecular level which showed homologous recombination between amplicons, affecting spermatogenesis process. There are novel methods and commercially available kits for accurate screening and characterization of microdeletions. It is important to detect the AZFc microdeletions through genetic screening and counseling those infertile men who planned to avail assisted reproduction techniques such as undergoing intracytoplasmic sperm injection or in vitro fertilization.